Using expressed behaviour of coho salmon (Oncorhynchus kisutch) to evaluate the vulnerability of upriver migrants under future hydrological regimes: Management implications and conservation planning. Issue 7 (6th February 2019) - Flitcroft, Rebecca; Lewis, Sarah; Arismendi, Ivan; Davis, Chante; Giannico, Guillermo; Penaluna, Brooke; Santelmann, Mary; Safeeq, Mohammad; Snyder, Jeff
Abstract: Globally, river systems have been extensively modified through alterations in riverscapes and flow regimes, reducing their capacity to absorb geophysical and environmental changes. In western North America and elsewhere, alterations in natural flow regimes and swimways through dams, levees, and floodplain development, work in concert with fire regime, forest management practices, as well as agriculture and urban development, to change recovery trajectories of river systems. Hydroregime scenarios for coho salmon, Oncorhynchus kisutch (Walbaum, 1792), were investigated in Washington and Oregon, USA, where long‐term records of discharge, water temperature, and upstream fish passage are available. This novel approach combines hydrological and ecological data in a single visualization, providing empirical foundations for understanding upstream behavioural movement and tolerances of native fishes. The timing of coho salmon movement with respect to temperature and discharge were compared with scenarios representing possible future hydrological conditions associated with a changing climate. This approach provides a framework for the study of future hydrological alterations in other locations, and can inform local and regional conservation planning, particularly in view of water management policy. Management implications and recommendations for action that may expand the capacity of riverscapes to absorb perturbations are discussed.